2005
DOI: 10.1016/j.ecolind.2004.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Ability of taxonomic diversity indices to discriminate coastal lagoon environments based on macrophyte communities

Abstract: Lagoons are highly productive areas representing more than 50% of the coastline area in Languedoc-Roussillon (South of France, Mediterranean sea). These lagoons are very different in their environmental conditions, human influences, eutrophication levels and aquaculture intensity. Based on macrophyte communities associated with soft substrates, two indices of taxonomic diversity (the "average taxonomic distinctness" (Δ+) and the "variation in taxonomic distinctness" (Λ+)) were used to discriminate four of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 57 publications
(56 reference statements)
3
55
0
3
Order By: Relevance
“…There has been increasing evidence that the taxonomic distinctness measures present an apparent insensitivity to sampling effort and sample size compared with traditional biodiversity measures Mouillot et al, 2005;Clarke & Gorley, 2006;Leonard et al, 2006;Prato et al, 2009). Furthermore, the taxonomic distinctness indices have a number of desirable properties as a measure of biodiversity in assessment of environmental stress, especially if coupled with a statistical framework for the assessment of the significance of departure from expectation (Warwick & Clarke, 1995Mouillot et al, 2005;Clarke & Gorley, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been increasing evidence that the taxonomic distinctness measures present an apparent insensitivity to sampling effort and sample size compared with traditional biodiversity measures Mouillot et al, 2005;Clarke & Gorley, 2006;Leonard et al, 2006;Prato et al, 2009). Furthermore, the taxonomic distinctness indices have a number of desirable properties as a measure of biodiversity in assessment of environmental stress, especially if coupled with a statistical framework for the assessment of the significance of departure from expectation (Warwick & Clarke, 1995Mouillot et al, 2005;Clarke & Gorley, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the taxonomic distinctness indices have a number of desirable properties as a measure of biodiversity in assessment of environmental stress, especially if coupled with a statistical framework for the assessment of the significance of departure from expectation (Warwick & Clarke, 1995Mouillot et al, 2005;Clarke & Gorley, 2006). Many previous researches on metazoan fauna have demonstrated that the taxonomic distinctness measures showed less sensitivity to natural habitat type but more to anthropogenic impacts (Mouillot et al, 2005; Leonard et al, 2006). Based on our present data, the average taxonomic distinctness of protozoan communities was significantly correlated with pollution/ eutrophication levels in flowing waters.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, our results imply that both the magnitude and the seasonality of seafloor POC flux impact the average taxonomic distinctness within nematode communities, which may be translated to a greater functional distinctness. However, since taxonomic distinctness may be governed by a variety of factors, such as biogeography, environmental factors, habitat characteristics, and stress (Bevilacqua et al, 2012;Leira et al, 2009;Mouillot et al, 2005;Clarke, 1995, 1998;Xu et al, 2011), more research into life history strategies, niche requirements and taxon interactions are needed to fully understand the patterns observed here. Unlike Leduc et al (2011) (nematode species and genera) and Etter and Grassle (1992) (macrofaunal species), we did not detect an effect of sediment heterogeneity (SED) on nematode genus diversity.…”
Section: Environmental Drivers Of Nematode Diversitymentioning
confidence: 99%
“…They show similar annual ranges in water temperatures (between 2 to 5 and 26 to 30°C, with a common meañ 17°C) and all have higher annual productivity levels and, from May to October, 1 to 5°C higher water temperatures than the sea (Table 1). Yet they differ in the chemical composition of their water masses because of different continental and marine influences, anthropogenic loads, and catchment areas (Mouillot et al 2005a). …”
Section: Study Areamentioning
confidence: 99%